Uwarunkowania rozwoju stosunków finansowo-kredytowych krajów bloku radzieckiego z Zachodem w latach 80. XX wieku - Klimiuk, Zbigniew (Przegląd Wschodnioeuropejski, 2023)
Economic relations between Comecon countries led by the Soviet Union (communist bloc) and OECD countries (Western Europe, the USA, Canada and Japan) in the 1980s were characterized by deep stagnation in all areas of mutual cooperation. This was due to many negative factors interconnected in a short time. They were very diverse in terms of nature, range and durability of impact. The article contains an analysis of the development of the financial and credit relations of the Soviet bloc countries with the West in the 1980s in the existing political and economic conditions of East-West relations. The financial and credit dependence of the socialist countries was very clear and intense at that time. Its elimination or reduction as a result of the development of connections in other directions was only partially possible. Its negative impact also covered areas vital for individual economies. In addition, it was of a long-term nature, which made this type of dependence useful as an economic instrument for political purposes, both in the aspect of short-term and long-term pressure on the implementation of political intentions. When analyzing the entirety of East-West economic contacts, one cannot omit the problem of the debt of the Comecon countries, which largely determines the development of all areas of cooperation. In the 1980s, in Comecon-OECD credit relations, two trends clearly intersected: negative and positive. A negative trend was manifested in the increase in debt burdening the economies of many Central and Eastern European countries. This was caused by an increase in payment liabilities for servicing debts resulting from the postponement of loan repayment dates.